Cochlear implantation impairs intracochlear microcirculation and counteracts iNOS induction in guinea pigs - Ernst, Benjamin Philipp; Heinrich, Ulf-Rüdiger; Fries, Mathias; Meuser, Regina; Rader, Tobias; Eckrich, Jonas; Stauber, Roland H.; Strieth, Sebastian (Frontiers in Cellular Neuroscience, 2023)
Introduction Preservation of residual hearing remains a great challenge during cochlear implantation. Cochlear implant (CI) electrode array insertion induces changes in the microvasculature as well as nitric oxide (NO)-dependent vessel dysfunction which have been identified as possible mediators of residual hearing loss after cochlear implantation. Methods A total of 24 guinea pigs were randomized to receive either a CI (n = 12) or a sham procedure (sham) by performing a cochleostomy without electrode array insertion (n = 12). The hearing threshold was determined using frequency-specific compound action potentials. To gain visual access to the stria vascularis, a microscopic window was created in the osseous cochlear lateral wall. Cochlear blood flow (CBF) and cochlear microvascular permeability (CMP) were evaluated immediately after treatment, as well as after 1 and 2 h, respectively. Finally, cochleae were resected for subsequent immunohistochemical analysis of the iNOS expression. Results The sham control group showed no change in mean CBF after 1 h (104.2 ± 0.7%) and 2 h (100.8 ± 3.6%) compared to baseline. In contrast, cochlear implantation resulted in a significant continuous decrease in CBF after 1 h (78.8 ± 8.1%, p < 0.001) and 2 h (60.6 ± 11.3%, p < 0.001). Additionally, the CI group exhibited a significantly increased CMP (+44.9% compared to baseline, p < 0.0001) and a significant increase in median hearing threshold (20.4 vs. 2.5 dB SPL, p = 0.0009) compared to sham after 2 h. Intriguingly, the CI group showed significantly lower iNOS-expression levels in the organ of Corti (329.5 vs. 54.33 AU, p = 0.0003), stria vascularis (596.7 vs. 48.51 AU, p < 0.0001), interdental cells (564.0 vs. 109.1 AU, p = 0.0003) and limbus fibrocytes (119.4 vs. 18.69 AU, p = 0.0286). Conclusion Mechanical and NO-dependent microvascular dysfunction seem to play a pivotal role in residual hearing loss after CI electrode array insertion. This may be facilitated by the implantation associated decrease in iNOS expression. Therefore, stabilization of cochlear microcirculation could be a therapeutic strategy to preserve residual hearing.